Maintenance costs of male dominance and sexually antagonistic selection in the wild. (28th September 2018) - Boratyński, Zbyszek; Koskela, Esa; Mappes, Tapio; Mills, Suzanne C.; Mokkonen, Mikael
Abstract: Variation in dominance status determines male mating and reproductive success, but natural selection for male dominance can be detrimental or antagonistic for female performance, and ultimately their fitness. Attaining and maintaining a high dominance status in a population of competing individuals is physiologically costly for males. But how male dominance status is mediated by maintenance energetics is currently not well understood, nor are the corresponding effects of male energetics on his sisters recognized. We conducted laboratory and field experiments on rodent populations to test whether selective breeding for male dominance status (dominant vs. subordinate breeding lines) antagonistically affected basal metabolic rate (BMR) and fitness of females under wild conditions. Our results showed elevated BMR in females, but not in males, from the dominant breeding line. However, phenotypically dominant males from the subordinate breeding line had the highest BMR. Males from the dominant line with low BMR sired the most litters and offspring in the field. Similarly, females from the dominant selection line tended to have more offspring if they had lower BMR, while the opposite trend was found in females from the subordinate selection line. Females with high and low BMR reproduced most often, as indicated by a significant quadratic selection gradient. The increased female BMR resulting from selection for male dominance suggests genetic incompatibility between sexes in metabolism inheritance. Elevated BMR in behaviourally dominant males, but not in males from the dominant breeding line, suggests physiological costs in males not genetically suited for dominance. Fitness costs of elevated maintenance costs (measured as BMR) shown here support the energetic compensation hypothesis where high BMR is selected against as it would trade off energy required for other important life‐history attributes. Aplain language summary is available for this article. Abstract : Plain Language Summary